Stardust Final Conference Advances in Asteroids and Space Debris Engineering and Science (Astrophysics and Space Science Proceedings,, 2018)
Space debris and asteroid impacts pose a very real, very near-term threat to Earth. In order to help study and mitigate these risks, the Stardust program was formed in 2013. This training and research network was devoted to developing and mastering techniques such as removal, deflection, exploitation, and tracking. This book is a collection of many of the topics addressed at the Final Stardust Conference, describing the latest in asteroid monitoring and how engineering efforts can help us reduce space debris. It is a selection of studies bringing together specialists from universities, research institutions, and industry, tasked with the mission of pushing the boundaries of space research with innovative ideas and visionary concepts. Topics covered by the Symposium: Orbital and Attitude Dynamics Modeling Long Term Orbit and Attitude Evolution Particle Cloud Modeling and Simulation Collision and Impact Modelling and Simulation, Re-entry Modeling and Simulation Asteroid Origins and Characterization Orbit and Attitude Determination Impact Prediction and Risk Analysis, Mission Analysis- Proximity Operations, Active Removal/Deflection Control Under Uncertainty, Active Removal/Deflection Technologies, and Asteroid Manipulation.